Optimal control mathematical model of Zika Virus - Budi Cahyono; Muhammad Abdurrahman Rois (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2020)
This study aims to describe the transmission of the Zika virus a mathematical model that was introduced by Ding, Tao, and Zhu (2016). Based on the analysis, obtained a disease-free equilibrium point, then the stability is seen from the basic reproduction number. The basic reproduction numbers show supporting factors and inhibitors of transmission of Zika virus. Then looking for optimal control, the principle is to control transmission of the Zika virus through reducing interactions between mosquitoes and humans, transmission from infected mosquitoes to susceptible humans, and estimates of mosquito deaths by being given insecticides. With the optimal control solution obtained, it produces a strategy to prevent and control the Zika virus and does not incur expensive costs.©2020 JNSMR UIN Walisongo. All rights reserved.